2006
DOI: 10.1007/s10661-006-9316-4
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Concentrations in Benthic Invertebrates from Amchitka and Kiska Islands in the Aleutian Chain, Alaska

Abstract: Concentrations of 13 radionuclides (137Cs, 129I, 60Co, 152Eu, 90Sr, 99Tc, 241Am, 238Pu, 239,249Pu, 234U, 235U, 236U, 238U) were examined in seven species of invertebrates from Amchitka and Kiska Islands, in the Aleutian Chain of Alaska, using gamma spectroscopy, inductively coupled plasma mass spectroscopy, and alpha spectroscopy. Amchitka Island was the site of three underground nuclear test (1965-1971), and we tested the null hypotheses that there were no differences in radionuclide concentrations between Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The use of marine organisms for monitoring radionuclide contamination is well established (Valette-Silver and Lauenstein, 1995;Burger et al, 2007;Thébault et al, 2008). In order to understand field measurements, the characterization of bioaccumulation parameters and/or investigations on the relative importance of the different exposure pathways has been carried out for several radionuclides Wang et al, 2000;Baines et al, 2005;Borretzen and Salbu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The use of marine organisms for monitoring radionuclide contamination is well established (Valette-Silver and Lauenstein, 1995;Burger et al, 2007;Thébault et al, 2008). In order to understand field measurements, the characterization of bioaccumulation parameters and/or investigations on the relative importance of the different exposure pathways has been carried out for several radionuclides Wang et al, 2000;Baines et al, 2005;Borretzen and Salbu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A sixth species, the echinoid Sphaerechinus granularis, contained 0.13 mg Riley and Segar, 1970;2, Leatherland and Burton, 1974;3, De Clerck et al, 1979;4, Eustace, 1974;5, Stenner and Nickless, 1974;6, Thompson and Paton, 1978;7, Bohn, 1979;8, Vattuone et al, 1976;9, Denton et al, 2006;10, Deudero et al, 2007. Cs/kg DW whole animal (Papadopoulu et al, 1976). Radiocesium-137 levels were below the minimum detection limit in the green sea urchin, Strongylocentrotus polyacanthus, collected from the Aleutian Islands in summer 2004: the site of nuclear tests between 1965 and 1971 (Burger et al, 2007b).…”
Section: Cesiummentioning
confidence: 90%
“…The dispute was resolved by bringing in an outside consortium of scientists (Consortium for Risk Evaluation with Stakeholder Participation [CRESP]) to design a Science Plan to develop the missing data to determine whether the food chain was safe (CRESP, 2003; Burger et al, 2005), and to conduct a research expedition to collect biota for radionuclide analysis (Powers et al, 2004). The results of the scientific studies indicated that the subsistence foods and commercial fish were free of radionuclides from the nuclear test, but could provide no assurance that the foods would continue to be safe (Burger et al, 2007e,f,g). The data were used to develop a biomonitoring plan that included subsistence foods and commercial fish (Burger, 2007a,b,c; Burger et al, 2007c) that was incorporated into the DOE long-term stewardship plan for Amchitka (DOE, 2008b).…”
Section: Case Studies: Points Of Confusion For Tribal Nations Govmentioning
confidence: 99%